PRECISION FARMING SOFTWARE TO MONITOR ENVIRONMENTAL THERMAL COMFORT PARAMETERS IN DAIRY CATTLE - MOLLO NETO, Mario; Nääs, I. de A. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Brazilian agriculture needs to introduce new technologies for administrative support, breaking with traditional practices and enabling the emergence of new management approaches. A known stressor related to environmental indicators, which is the temperature and humidity index (THI) cause production losses and need to be properly monitored to avoid depress the performance of dairy cows. In this sense, based on four categories of ITU, as a function of values ​​obtained from climatological analysis of heat, this study aimed to develop an application for Windows operating environment that allows the monitoring of index values ​​for temperature and humidity.